Blood flow restriction during training for improving the aerobic capacity and sport performance of trained athletes: A systematic review and meta-analysis - Castilla-López, C.; Molina-Mula, J.; Romero-Franco, N. (Journal of Exercise Science & Fitness, 2022)
Background/Objective: Combining blood flow restriction (BFR) with endurance training is exponentially increasing although the benefits are unclear in trained athletes. We aimed to describe the effects of aerobic and/or anaerobic training programmes combined with BFR on the aerobic capacity and related sport performance of trained athletes. Methods: Databases used were MEDLINE, SPORTDiscus, LILACS, IBECS, CINHAL, COCHRANE, SCIELO and PEDro, through October 2021. For study selection, criteria included (a) clinical trials that recruited trained healthy athletes, that (b) proposed BFR in combination with aerobic/anaerobic training programmes (=8 sessions) and that (c) evaluated either aerobic capacity or related sport performance. For data extraction, a reviewer extracted the data, and another reviewer independently verified it. The tool RoB 2 (Risk of bias 2) was used to assess risk of bias. Results: Ten studies met the eligibility criteria, capturing a total of 207 participants. Although it did not reveal any significant effects from training with BFR on aerobic capacity compared to the same training without BFR, effect sizes were extremely high. Subgroup analyses according to the intensity of the training programmes found similar results for low-to-moderate or high-intensity training compared to the same sessions without BFR. Conclusion: Although adding BFR to training sessions always produce benefits from baseline in aerobic capacity and sport performance of trained athletes, these results are not better than those observed after the same training sessions without BFR. The reduced number of studies, small sample sizes and some concerns regarding risk of bias should be highlighted as limitations.